2019
DOI: 10.1042/bsr20181809
|View full text |Cite
|
Sign up to set email alerts
|

The association ofFOXP3gene polymorphisms with cancer susceptibility: a comprehensive systemic review and meta-analysis

Abstract: The role of forkhead box P3 (FOXP3) protein in tumorigenesis has long been controversial and existing data on the association between FOXP3 gene polymorphisms and cancer susceptibility were inconsistent. Here, we conducted a meta-analysis to better clarify the relationship. A comprehensive search of studies published from July 2008 to June 2018 was conducted. The statistical analyses of the pooled odds ratios (ORs) and the corresponding 95% confidence intervals (95% CIs) were performed using the Revman 5.2 sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…15 FOXP3 is encoded by FOXP3 (Scurfin) gene (Gene ID: 50943, MIM #300292), and acts both as an activator of transcription for Treg cells development, and as a transcriptional repressor in downregulating cytokine expression. 16,17 FOXP3 gene is located on chromosome Xp11.23, 17 and several FOXP3 polymorphisms associated with different diseases, particularly those associated with altered immunity, were reported. These include systemic lupus erythematosus, 18,19 Grave's disease, 20,21 type 1 (autoimmune) diabetes mellitus, and allergic rhinitis, 22,23 and pregnancy complications, including preeclampsia, 24,25 and RPL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 FOXP3 is encoded by FOXP3 (Scurfin) gene (Gene ID: 50943, MIM #300292), and acts both as an activator of transcription for Treg cells development, and as a transcriptional repressor in downregulating cytokine expression. 16,17 FOXP3 gene is located on chromosome Xp11.23, 17 and several FOXP3 polymorphisms associated with different diseases, particularly those associated with altered immunity, were reported. These include systemic lupus erythematosus, 18,19 Grave's disease, 20,21 type 1 (autoimmune) diabetes mellitus, and allergic rhinitis, 22,23 and pregnancy complications, including preeclampsia, 24,25 and RPL.…”
Section: Introductionmentioning
confidence: 99%
“…FOXP3 is encoded by FOXP3 ( Scurfin ) gene (Gene ID: 50943, MIM #300292), and acts both as an activator of transcription for Treg cells development, and as a transcriptional repressor in downregulating cytokine expression 16,17 . FOXP3 gene is located on chromosome Xp11.23, 17 and several FOXP3 polymorphisms associated with different diseases, particularly those associated with altered immunity, were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these limitations, the current outcomes should be interpreted with caution and the conclusions of this meta-analysis require detailed consideration. [60][61][62] In conclusion. this current systematic review and meta-analysis demonstrated that FOXF2 may be a clinically important prognostic factor for patients with various types of cancer prone to bone metastasis.…”
Section: Discussionmentioning
confidence: 74%
“…As an important component of the tumour microenvironment, Tregs are responsible for the downregulation of autoimmune reactions and promotion of immunological tolerance. Recent studies on the roles of Tregs in tumours have demonstrated that the regulatory mechanisms mediated by Tregs contribute to immune evasion against tumour immunotherapy 10 . Therefore, FOXP3 is an essential factor that induces and maintains the unique immunosuppressive properties of Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the roles of Tregs in tumours have demonstrated that the regulatory mechanisms mediated by Tregs contribute to immune evasion against tumour immunotherapy. 10 Therefore, FOXP3 is an essential factor that induces and maintains the unique immunosuppressive properties of Tregs.…”
mentioning
confidence: 99%